The Study and Analysis of Verbal Thoughts of Attar Neishabouri (Looking at his Masnavi) - Mohammad Ali Jahani Ghadi; Reza Fahimi; Malek Mohammad Farokhzad (Matn/Pizhūhī-i Adabī, 2023)
The influence of theology and verbal thoughts in Persian literature is an undeniable issue, so we can observe the majority of verbal subjects in mystical works. In this study, we consider verbal scopes of Attar in his Masnavi including verbal theism and belief in behavioral determinism and wisdom dysfunction. In the conception of narrative virtue, indecency, absolute purity, and divine grace and resurrection are the most important verbal concepts of Attar in Masnavi. But it is noticeable that Attar did not accept different verbal thoughts absolutely. In other words, Attar's perspectives incorporated gnostic scopes and verbal theories. For example, in the field of theism, he believed in a beloved, lovable, and kind God while most poets knew his wrathful and unmerciful features that whatever he does is mere justice. Generally, it could be said that although Attar had the same views as other poets, in some cases, one can see ideas different from the other poets’ ideas in his works.